Inelastic photoproduction at HERA: A second charmonium crisis? - Éboli, O. J P [UNESP]; Gregores, E. M.; Halzen, F. (Elsevier, 1999)
Measurements of the inelastic photoproduction of charmonium at HERA have ignited a new charmonium crisis. The Color Singlet approach to computing onium production cross sections fits the data for large charmonium energy fraction z, where color octet models fail. This approach is however in qualitative disagreement with a wealth of information that exist on charmonium production by other initial states. We here suggest that the source of the discrepancy between color octet models (whether implemented in the soft color or NRQCD formalism) and data is due to the neglect of non-perturbative effects. Implementing these in a scheme originally developed for Drell-Yan phenomenology, we illustrate how agreement with the data is achieved. © 1999 Elsevier Science B.V. All rights reserved.